Efektifitas Penggunaan Metode Bernyanyi Lagu “Tebak Aku” dalam Pengenalan Huruf Vokal Pada Anak Usia Dini - Nina Nuriyah Ma'arif; Rizka Kurniawati (Prodi Pendidikan Islam Anak Usia Dini Institut Agama Islam Daruttaqwa Gresik, 2022)
This article discusses the effectiveness of using the method of singing the song “Tebak Aku” in improving students' understanding about vowels letter for early child aged 3-4 years in KBIP Al-Muchlisin Gresik. This study uses a quantitative research experiment, namely one group pre-test and post-test design. In order to test the hypothesis whether or not there is a significant increase in the ability to recognize vowels before and after using the method singing the song “Tebak Aku”, this research utilises t-test for analysing the data. The findings have revealed that there is a significant increase in children's ability with regard to recognise vowels before and after using the method of singing the song